From ethnic prejudice to ethnic solidarity: representation of muslim women in pre-independence Indonesian peranakan Chinese literature - Dewojati, Cahyaningrum; Arifin, Moch. Zainul (Penerbit Universiti Kebangsaan Malaysia, 2024)
Javanese women, particularly Muslim women, in the colonial era were often portrayed as passive, gentle, obedient, and powerless parties. Whereas Muslim women also took part in the resistance movement against tradition and the oppressive colonial system. Studies on the representation of Muslim women in the colonial era are generally studied from manuscripts and literary works from the palace, and rarely from Indonesian Peranakan Chinese literature. This article aims to fill this gap by examining the representation of Muslim women in Peranakan Chinese literature in the Indonesian pre-independence era, the golden age of Peranakan Chinese literature. To understand the shift in the portrayal of Muslim women, the research employed Nielsen’s theory of ethnic solidarity and Lugones’ decolonial feminism. As a research approach, Fairclough's Critical discourse analysis (CDA) was applied. The findings of this study were that the representations of Muslim women in the texts of Peranakan Chinese literature varied in each decade. In the 1910s, Muslim women were represented as Javanese women with aristocratic social class (priyayi), European-educated, but irrational. In addition, Muslim women were positioned as a lower social class, namely servants in Chinese families. Meanwhile, in the 1920s, Muslim women were not only servants in Chinese families but were also illiterate and easy to be bribed. Both eras showed the existence of ethnic prejudice and the coloniality of gender. In the era leading up to Indonesian independence in the 1930s to be precise, Muslim women were portrayed as embodying decolonial subjectivity and as parties capable of fighting alongside other ethnicities, notably the Chinese, against the Dutch colonial authorities. As a result, ethnic prejudice has diminished and been replaced by ethnic unity. These ethnic groups are acknowledged as Indonesian citizens via decolonial subjectivity.